2018
DOI: 10.1016/j.ijpharm.2018.03.031
|View full text |Cite
|
Sign up to set email alerts
|

3D printed microneedles for insulin skin delivery

Abstract: In this study, polymeric microneedle patches were fabricated by stereolithography, a 3D printing technique, for the transdermal delivery of insulin. A biocompatible resin was photopolymerized to build pyramid and cone microneedle designs followed by inkjet print coating of insulin formulations. Trehalose, mannitol and xylitol were used as drug carriers with the aim to preserve insulin integrity and stability but also to facilitate rapid release rates. Circular dichroism and Raman analysis demonstrated that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
181
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(186 citation statements)
references
References 37 publications
4
181
0
1
Order By: Relevance
“…Figure 1F is the optical microscopic image of the GelMA MN patch, which showed an 11 × 11 array of uniformly aligned MNs fixed on a 1 cm × 1 cm patch to support sufficient ISF extraction for later analysis. The most commonly used techniques to manufacture MNs with different shapes and sizes include micromolding,30 lithography,31 laser cutting,32 3D printing,33 and wet or dry etching 34. In the present work, we used a polydimethylsiloxane (PDMS) mold with a predesigned shape and size to manufacture the MN patches.…”
Section: Figurementioning
confidence: 99%
“…Figure 1F is the optical microscopic image of the GelMA MN patch, which showed an 11 × 11 array of uniformly aligned MNs fixed on a 1 cm × 1 cm patch to support sufficient ISF extraction for later analysis. The most commonly used techniques to manufacture MNs with different shapes and sizes include micromolding,30 lithography,31 laser cutting,32 3D printing,33 and wet or dry etching 34. In the present work, we used a polydimethylsiloxane (PDMS) mold with a predesigned shape and size to manufacture the MN patches.…”
Section: Figurementioning
confidence: 99%
“…CAE files are digitalized representations of conical MNs. Conical MNs are produced in MicroChem (SU-8 photoresist) via UV exposure 21,47,48 (Fig. 1A).…”
Section: Materials Polyvinyl Pyrrolidone K-30 (Pvp K-30) Was Kindly mentioning
confidence: 99%
“…The study also showed the degradability of polylactic acid (a renewable, biodegradable, and thermoplastic polymer) in the skin, leading to the drug release (Luzuriaga et al 2018). Pere et al (2018) also fabricated biocompatible polymeric microneedle patches for insulin skin delivery. Using the SLA method, a biocompatible resin was photopolymerized to make microneedles of cone and pyramid geometries, followed by IJ print coating of insulin formulations.…”
Section: Microneedlesmentioning
confidence: 91%